2019
DOI: 10.1186/s40479-019-0103-6
|View full text |Cite
|
Sign up to set email alerts
|

Low positive affect display mediates the association between borderline personality disorder and negative evaluations at zero acquaintance

Abstract: Background Several recent studies have demonstrated that naïve raters tend to evaluate individuals with Borderline Personality Disorder (BPD) negatively at zero-acquaintance (i.e., in a ‘first impression’ type situation, where the rater has no knowledge of the individual and no prior interactions with them). Specifically, individuals with BPD were evaluated as less trustworthy, likeable, and cooperative than healthy participants (HCs). Based on previous impression formation studies, we hypothesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…In a first step, we examined general facial affective behavior. Corresponding to the results of Benecke and Dammann (2004) , Renneberg et al (2005) , Buchheim et al (2007) , and Hepp et al (2019) , we found a high amount of negative facial affects such as disgust and contempt in our patients. The highest score was found for disgust, which seems to be the predominant emotion for these patients ( Krause, 1998 ; Benecke and Dammann, 2004 ; Buchheim et al, 2007 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In a first step, we examined general facial affective behavior. Corresponding to the results of Benecke and Dammann (2004) , Renneberg et al (2005) , Buchheim et al (2007) , and Hepp et al (2019) , we found a high amount of negative facial affects such as disgust and contempt in our patients. The highest score was found for disgust, which seems to be the predominant emotion for these patients ( Krause, 1998 ; Benecke and Dammann, 2004 ; Buchheim et al, 2007 ).…”
Section: Discussionsupporting
confidence: 91%
“…Presumably, patients with BPD are chronically in a mental state of being too close to something negative or threatening. The predominance of facial disgust expressions might contribute to the described interpersonal problems of these groups of patients by eliciting negative evaluation (Hepp et al, 2019). In a similar vein, Benecke et al (2011) described a maladaptive cycle of easily triggered internal affective states (e.g., passive-negative affect, such as fear or despair) in patients with severe mental disorders based on problematic former relationship experiences.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We were interested whether targets with BPD would be perceived differently than HC targets and found that individuals with BPD were perceived more negatively than HCs [ 54 ]. Next, we asked a third sample of students to rate observable behavioral cues for all targets, e.g., amount of eye-contact with the camera, and used this as a mediator for the previously observed negative ratings [ 53 ]. Thus, all studies in phase II investigated BPD individuals as targets .…”
Section: Methodsmentioning
confidence: 99%